EFEKTIVITAS JUS PISANG DAN AIR KELAPA MUDA TERHADAP TENSI LANSIA PENDERITA HIPERTENSI - Tri Peni; Sulis Diana (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2015)
Banana and coconut water contains high levels of potassium which can help lower blood pressure by binding sodium in the blood to be removed through the urine. This study aims to prove the effect of the combination of banana and coconut juice on blood pressure in Panti Wreda Mojopahit Mojokerto. Researchers use quasy research design. The sample is hypertensive patients as many as 20 people were selected using purpoosive sampling, which are divided into 2 groups of 10 people were given the combination juice of young coconut water and bananas and 10 people as control were treated for 5 days. Data tension every 30 minutes after treatment were collected and analyzed using the Friedman test and the Mann Whitney test. The study concluded that there are differences in systolic and diastolic blood pressure before and after the given combination juice of young coconut water and bananas.The systolic blood pressure between juice and coconut water group are significantly different, but the diastolic blood pressure was not found any difference in the two groups. Therefore concluded that the combination is more effective of the juice affects the systolic than diastolic blood pressure.